The cost benefit analysis of the implementation of photovoltaic solar system in Saudi Arabia - Mouawad, Mariam (Université d'Ottawa | University of Ottawa, 2019)
The Middle Eastern Kingdom of Saudi Arabia (KSA) is the 14th largest country in the world and one of countries that burn crude oil directly for power generation. In response to the rising costs of the fossil fuels used in generating the electricity required to meet its continuously increasing electricity demand and the negative environmental impact of burning fossil fuels, Saudi Arabia is planning to more than double its available generating capacity from 58 GW to 120 GW by developing solar and nuclear power generation. This paper demonstrates the economic feasibility and viability of a 3.5 MW photovoltaic solar energy station at the investment cost of $4/kW, 15% efficiency, and 10% interest rate. A cost-benefit analysis demonstrates that when the savings in fossil fuels and the decrease in CO2 emissions of an oil-fired generating plant are taken into account, the levelized cost of electricity of a photovoltaic solar energy system and that of an oil-fired generating plant are the same at $0.07/kWh. The results of the cost-benefit analysis is further strengthened when one looks at the learning curve of the photovoltaic technology, which predicts that the levelized cost of electricity of a photovoltaic solar energy system will be lower than that of any traditional technology used in generating electricity, including coal-fired and gas-fired generating plants.